A bibliometric perspective on the role of circular economy in achieving sustainable development goals - Abhinav Pal; Dolly Gaur; Pranav Raj; Kanishka Gupta; Chandan Kumar Tiwari (Discover Sustainability)
Abstract This study delves into the impact, quality, and volume of research publications regarding the significance of the circular economy (CE) in attaining the Sustainable Development Goals (SDGs) established by the United Nations (UN). To this end, bibliographic records were retrieved from the Scopus database. The initial analysis indicated that the majority of research available on Scopus database originates from Italy, China, and Spain, in that order. The study utilized K-structure analysis along with bibliometrics to map and underscore the aspects of intellectuality, conceptual framework, and social K-structure. The Bibliometrix package in R-Studio (version 4.3.3) along with VOSviewer was used to conduct bibliometric analysis. This method facilitated the mapping and sub-theme analysis of SDGs within the circular economy framework. The findings indicated a significant increase in circular economy (CE) research, with a 17.58% annual growth rate since the adoption of the Sustainable Development Goals (SDGs) in 2015. This growth mirrors CE’s increasing prominence in sustainability conversations. Despite ongoing efforts by countries like China and Spain, international collaboration remains limited. Notable areas of research include waste management, sustainability, and resource efficiency, alongside an emerging interest in digital transformation and circular supply chains. The industry is transitioning to SDG-aligned strategies that extend beyond the recycling-focused initiatives of the past. However, the study notes a lack of strong theoretical foundations and insufficient integration with public policy, calling for interdisciplinary advancement.